2011
DOI: 10.1007/s11269-011-9920-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Demand Driven Hydro-climatic Model for Drought Planning

Abstract: In recent years, droughts with increasing severity and frequency have been experienced around the world due to climate change effects. Water planning and management during droughts needs to deal with water demand variability, uncertainties in streamflow prediction, conflicts over water resources allocation, and the absence of necessary emergency schemes in drought situations. Reservoirs could play an important role in drought mitigation; therefore, development of an algorithm for operation of reservoirs in dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
(40 reference statements)
0
10
0
1
Order By: Relevance
“…They found that preserving water before drought should be judged carefully, especially in the regions where the evaporation rate was high. Karamouz et al [20] applied hedging based optimization model to a reservoir, which served domestic, industrial, and irrigation demands. They obtained hedging rules based on precipitation, temperature, and generated stream ow.…”
Section: Hedging Rules For Reservoir Operationmentioning
confidence: 99%
“…They found that preserving water before drought should be judged carefully, especially in the regions where the evaporation rate was high. Karamouz et al [20] applied hedging based optimization model to a reservoir, which served domestic, industrial, and irrigation demands. They obtained hedging rules based on precipitation, temperature, and generated stream ow.…”
Section: Hedging Rules For Reservoir Operationmentioning
confidence: 99%
“…The research shows that the reservoir is adaptable to climate changes (Yao and Georgakakos, 2001). In other researches, Maurer et al (2009) and Karamouz et al (2012) investigated effects of climate change on reliability of reservoirs using outputs of the emission scenarios A2 and B2 of GCM model. Their research indicates reduction of capacity of hydropower and water supply under climate change (Karamouz et al, 2012;Maurer et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Different forms of hedging rules used for domestic and irrigation supply for the past few decades and Neelakantan and Sasireka [15] review paper and Sasireka and Neelakantan [16,17]shows different forms of hedging rules proposed for domestic, irrigation and hydropower generation purpose. Karamouz et al [18] developed a contingency planning scheme by incorporating hedging rule in the operation of reservoirs in drought periods to reduce the effect of water deficit. Almost all the reported works which used hedging rule for reservoir operation considered either drinking water demand or irrigation demand or both together.…”
Section: Introductionmentioning
confidence: 99%